2013
DOI: 10.3168/jds.2012-6464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weekly regrouping of prepartum dairy cows on metabolic, health, reproductive, and productive parameters

Abstract: The objectives of the current experiment were to determine the effect of 2 prepartum grouping strategies on the health, metabolic, reproductive, and productive parameters of dairy cows. Jersey cows enrolled in the experiment at 253±3 d of gestation (d 0=calving) were balanced for parity and projected 305-d mature equivalent and assigned to 1 of 2 treatments. Cows assigned to the traditional (TRD; n=6 replicates with a total of 308 cows) treatment were moved to the study pen as a group of 44 cows and weekly the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…There was no main effect of lying and feeding space allowance on measures of neutrophil function, similar to Silva et al (2013b), who evaluated the percentage of neutrophils positive for phagocytosis or oxidative burst among a subgroup of 68 Jersey cows housed in a stable housing group with no further additions or a traditional close-up group with weekly additions of animals. When C_Ind category was offered to the oxidative burst model in the present study, a treatment × C_Ind interaction showed that although oxidative burst function was similar between competition categories in the overstocked groups, cows in the understocked group with a moderate or high C_Ind had greater oxidative burst function than low-ranking cows and overstocked cows.…”
Section: Discussionmentioning
confidence: 58%
“…There was no main effect of lying and feeding space allowance on measures of neutrophil function, similar to Silva et al (2013b), who evaluated the percentage of neutrophils positive for phagocytosis or oxidative burst among a subgroup of 68 Jersey cows housed in a stable housing group with no further additions or a traditional close-up group with weekly additions of animals. When C_Ind category was offered to the oxidative burst model in the present study, a treatment × C_Ind interaction showed that although oxidative burst function was similar between competition categories in the overstocked groups, cows in the understocked group with a moderate or high C_Ind had greater oxidative burst function than low-ranking cows and overstocked cows.…”
Section: Discussionmentioning
confidence: 58%
“…For example, Huzzey et al (2012) found that cows housed in overstocked pens (200% stocking: 0.5 lying stalls/cow and 34.5 cm linear feed bunk space/cow) had higher circulating NEFA and glucose concentrations during the early dry period compared with cows housed at 100% stocking (1 lying stall/cow and 68.5 cm linear feed bunk space/cow). In contrast, Silva et al (2013) found that regrouping cows weekly did not affect NEFA or BHB compared with stable groups before calving. Similarly, Coonen et al (2011) found no effect of twice-weekly regroupings before calving on NEFA compared with stable groups.…”
Section: Discussionmentioning
confidence: 68%
“…These links are thought to be mediated largely through glucocorticoid and catecholamine signaling originating in the central nervous system (Chida et al, 2006). This area of investigation is worth mentioning because of the many social stressors for cows during the transition to lactation, although there has been little concrete evidence that minimizing group disruptions can improve health or production outcomes when stocking rates are appropriate (Silva et al, 2013). Another potential contributor to systemic inflamma-tion is heat stress.…”
Section: Prevalence and Causes Of Inflammation During The Transition mentioning
confidence: 99%